Motives and interests of power. Behind Anies Baswedan’s populist political communication style as a government political actor - Daryani; Udi Rusadi; Asrul Mustaqim (Technium Social Sciences Journal, 2024)
This research was conducted with the aim of identifying Anies Baswedan’s populist political communication style as a government political actor and uncovering the motives and interests of power behind its use by using theory of populism and Burke’s dramatism. This research has a critical paradigm with a qualitative research design. The data collection method consists of in-depth interviews (in dept interviews); observation; literature and document study; and triangulation. The research quality criteria are based on historical situatedness. The research results show that the populist political communication style of government political actors is a symbolic action of a leader born from the democratic process. The component of the populist political communication style that is prominently used is the pro-people component. The motive revealed was the desire to build alternative political power through image and public opinion. Meanwhile, the interests of power are to protect and strengthen the legitimacy of the leadership to maintain power and pave the way for political career advancement. A number of findings which are novel in this research are the populist dramatism approach as a synthesis of the theories of dramatism and populism; audience’s perception as an additional element in the analysis of the Burkeian dramatic pentad; and identification and cross-check methods to determine the appropriate scene for the rhetorical act of political speech.